Sustaining faculty organizational development through teambuilding activities. - Ismail, Ismi Arif; Ab Jalil, Habibah; Krauss, Steven Eric (2008)
Organizational development is a continuous effort at helping people to enjoy working together as a team towards reaching their individual and organizational goals (Argyris & Schon, 1978, 1996, French & Bell, 1995, Bolman & Deal, 1997). Team building activity is one of the mechanisms used by organization to develop sustainable organizational culture (Finger & Brand, 1999; Prichard & Ashleigh, 2007; Senge, 1990). Like other learning organizations, universities are also using team building activities in their organizational development exercises. It is interesting to unveil to what extent do team building activities which are normally carried out within and outside campus impact staff morale and spirit of working as a team. This study aims to evaluate the impact of team building activities on faculty organizational culture. This paper discusses the activities, characteristics, and outcomes of a team building program organized by a faculty. It describes and analyzes the planning, implementation and evaluation components of the whole teambuilding activity. The findings of the study contribute to the knowledge on how team building activities can assist universities in developing sustainable organizational culture in academia.